Competitive Analysis of the Hotel Industry in Konya by Using Porter’s Five Forces Model - Göral, Ramazan (European Journal of Economics and Business Studies, 2015)
One of the areas of industry in Konya which needs to be analyzed regarding effective factors on competition is hotel industry. Accordingly, the current research tries to analyze factors impacting on the industry using Porter's five forces model. According to this model, an industry is affected by five competitive forces and these forces determine the state of competitiveness and profitability of an industry. Porter’s model is based on the insight that a corporate strategy should meet the opportunities and threats in the organizations external environment. Especially, competitive strategy should base on and understanding of industry structures and the way they change. Porter has identified five competitive forces that shape every industry and every market: entry of new investors, threat of substitutes, bargaining power of buyers, bargaining power of suppliers, and rivalry among existing competitors. Porter’s model supports analysis of the driving forces in an industry. Based on the information derived from the Five Forces Analysis, management can decide how to influence or to exploit particular characteristics of their industry. This study aims to analyze the competitiveness at Konya Hotel Industry by using Porter’s Five Forces Model. In this study, questionnaires have been used for data collection. The statistical population of the research consists of managers of hotel business (Senior, middle, executives).
Keywords: Porter’s Five Forces, Threat of Entry, Power of Suppliers, Power of Buyers, Threat of Substitutes, Rivalry Among Existing Competitors.